ARCHITECTURAL LANDSCAPE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
The architectural landscape is a canvas upon which humanity paints its aspirations, values, and cultural identities. It represents the symbiotic relationship between built structures and the natural environment, where design choices harmonize or contrast with the surrounding landscape. In this essay, we delve into the multifaceted nature of architectural landscapes, exploring their historical evolution, cultural significance, and contemporary relevance.